Pengembangan Media Poster Edukasi Kesiapsiagaan Bencana untuk Siswa Sekolah Dasar - Pangestu, Poin Agus; Tisngati, Urip; Aristya, Ferry (PGSD STKIP PGRI Pacitan, 2022)
This research and development aim to determine: (1) the procedure of developing educational poster media for disaster preparedness for elementary schools; (2) the feasibility level of developing disaster preparedness educational poster media for elementary school students. This research was included in Research and Development (R&D) using the ADDIE development model developed by Dick & Carry (1996). Researchers limit the five stages to 4 stages of research steps carried out including: (1) the analysis stage, (2) the design stage, (3) the development stage, (4) the implementation stage. The product of this research has been validated by 5 experts consisting of media experts, material experts, and linguists and conducted a small-scale FGD (Focus Group Discussion) with several students from Sebelas Maret University. The results showed that: (1) Disaster preparedness educational poster media for elementary schools had been developed through 4 stages of the ADDIE development model developed by Dick & Carey; (2) the results of the media expert's assessment obtained an average of 4.8 with the